Toda criança é capaz de aprender: as contribuições de Edouard Séguin (1812-1880) para a educação da criança com deficiência intelectual - Rosa, Kaciana Nascimento da Silveira (2012)
This thesis consists in a study about the pedagogical experiences developed by the educator and doctor Edouard Séguin (1812 - 1880) in the process of teaching persons with intellectual deficiency during the age XIX. To the comprehension about the historical significance of the theoretic and practical material left by Edouard Séguin, it was necessary, initially, to do a historical study about the aspects relating to the special education area during the age XVIII e XIX, the period which others doctors also stood out in the treatment to persons with intellectual deficiency. Because it is a study about the theoretic character, it is considered the theoretic production in the special education area, observing the reading and the analysis of materials about the life, studies and experiences developed by Edouard Séguin, having as primary source the texts of his own authorship. It is taken as basis the two works which contains all of his work done with children and young with intellectual deficiency - Traitement moral, hygiène et éducation des idiots et des autres enfants arriérés and Idiocy and Its Treatment by the Physiological Method tracing its contributions to the education of persons with intellectual deficiency. Lastly, the most important aspects of Seguin s work which points to the constitution of special education are systematized, in particular about the education of person with intellectual deficiency